A Two-Phase Method for Solving Transportation Models with Prohibited Routes - Owusu-Ansah, Emmanuel; Ackora-Prah, Joseph; Acheson, Valentine; Barnes, Benedict; Takyi, Ishmael (Pakistan Journal of Statistics and Operation Research, 2024)
This article is published by Pakistan Journal of Statistics and Operation Research 2022 and is also available at http://dx.doi.org/10.18187/pjsor.v18i3.3911